THE PRINCIPLE OF GOOD FAITH IN COLLECTIVE LABOR AGREEMENTS BETWEEN EMPLOYERS AND LABOR UNIONS IN REVIEW OF CONTRACT LAW - Safrida Safrida (Universitas Labuhanbatu, 2024)
The principle of good faith is an important principle in contract law and is accepted in various legal systems, but until now the doctrine of good faith is still controversial Good faith is known by 2 (two) phases, namely the pre-contract phase and the contract execution phase. The pre-contract phase is called subjective good faith, which means that good faith is more directed towards honesty, while good faith in the contract implementation phase is called objective good faith, which means that good faith is interpreted as appropriateness and decency or justice. A work agreement is an agreement between workers/laborers and employers or employers that contains working conditions, rights and obligations for the parties. The definition of working conditions is the rights and obligations of employers and workers that have not been regulated in laws and regulations. Work agreements made must not conflict with existing labor agreements or Collective Labor Agreements (KKB)/Collective Labor Agreements (PKB). This research uses normative legal research sourced from secondary data related to the research topic, secondary data that has been systematically arranged and then analyzed qualitatively. From the research conducted, it was found that the position of the principle of good faith is very important not only at the stage of making (signing) and post-making (implementation) of the contract, but also at the pre-making (drafting) stage of the contract because in the practice of contract law the judge does use his authority to interfere with the contents of the contract. The legal consequences of a collective bargaining agreement that does not contain the principle of good faith are that if the subjective requirements concerning the subject of the CBA are incomplete, or in other words the requirements that must be met are not appropriate for those who want to make a CBA, then the CBA that has been made can be requested for cancellation by the trade union/labor union. If the cancellation is not requested by both parties concerned, then the PKB remains valid for the parties. The first legal effort made by PT United Rope with the labor union is by way of deliberation to reach consensus first, although in dispute resolution if there is no good faith in the collective labor agreement is through 2 (two) systems, namely first, non-litigation / outside the industrial relations court, namely bipartite settlement, mediation, conciliation and arbitration, while the second settlement is litigation.Keywords: Good Faith, Collective Labor Agreement; Businessman; Labour Union